DIGITAL TRANSFORMATION IN 2024 INDONESIAN ELECTION CAMPAIGNS: CONTENT ANALYSIS OF CANDIDATE BRANDING ON SOCIAL MEDIA - Ermila Kamil; Fitri Sundari (Academic Solution Publisher, 2024)
Indonesia in 2024 is experiencing an era of rapid technological development. This technological progress is referred to as digital transformation. In the 2024 election, digital transformation has created a new atmosphere in political campaigning one that is more adaptive and innovative in shaping candidates’ public images. In political campaigns, every party and presidential and vice-presidential candidate competes to build a favorable image in order to gain public attention. This study analyzes the campaign image of the 2024 election by examining the use of digital transformation. A qualitative approach is employed, using content analysis of the social media platforms utilized by the 2024 presidential and vice-presidential candidates. The use of technology in digital transformation within the 2024 election campaign is closely linked to the diffusion of innovation theory. The 2024 election reflects diffusion of innovation through the role of political communication in shaping the campaign image of each candidate. The use of social media, campaign organizing technologies, digital marketing strategies, along with visual and multimedia content, successfully created strong branding and effective political communication that was relevant and responsive in the 2024 election.